Multidisciplinary and Nonpharmacological Management of Pain in Temporomandibular Disorders (TMDs) - Elżbieta Kubala; Danuta Lietz–Kijak; Paulina Strzelecka; Aneta Wieczorek; Piotr Skomro; Helena Gronwald (Pain Research and Management)
Temporomandibular joint dysfunction (TMD) is not a single diagnosis, but a term covering a group of conditions that involve pain and dysfunction of the masticatory muscles within the temporomandibular joint (TMJ) and associated structures. It is a set of disease entities comprising various ailments and clinical symptoms. One of the most distressing symptoms for TMD patients is pain. Pain is subjective and always unpleasant. The VAS (visual analogue scale) was used in this research. The aim of this study was to assess the influence of physical stimuli, namely extremely low frequency magnetic field (ELF-MF) and LED light, on the experience of pain caused by increased tension in the masticatory muscles in adults. Out of 150 people examined, 104 were enrolled in the study after meeting the eligibility criteria. The study group was divided into 4 subgroups. Each subgroup received physical therapy treatment using a different physical stimulus. The effects of four therapeutic modalities were compared. In terms of VAS scores, pain attenuation was observed in all subgroups. The study confirmed the analgesic effect of the selected physical therapy methods. The authors focused on the analysis of the results obtained for each subgroup, comparing the effects of individual modalities on pain intensity (according to VAS scores). After the treatment, pain relief was observed in each of the studied subgroups. Treatment using ELF-MF and ELF-MF in combination with LED light in the course of TMD brings about a significant improvement in the subjective pain experience expressed in VAS pain scores. The use of selected physical stimuli and their beneficial effect on pain symptoms during mandibular movements has important implications for patients’ daily life and work. Incorporation of therapeutic methods can help enhance patient satisfaction and comfort during manual TMJ therapy and lengthy dental procedures.